(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
يقدم هذا البحث طريقة معينة لتحديد مستقرات بعض الداليات العقدية المختارة في فضاء كاراتيودوري وهو فضاء التوابع التحليلية في قرص الواحدة الذي يحقق الشرط وأيضاَ في فضاء الدوال النجمية المرتبط معه. باستخدام التمثيل التكاملي للدوال تم تحديد منطقة تحول بعض الداليات في كل من هذين الفضائين من الشكل . This paper presents a certain method of determining the range of variability of some linear functional defined by the Caratheodory Class (i.e. the class of analytic functions in the unit disk with a real positive part f(0)=1) and by the Class of Starlike Functions related to it. Using the integral representation of functions in these classes, some estimations for the functional of the type have been obtained.